Time Interval for Diagnosis of Tuberculosis and Related Expenditure in Selected Health Centers in Addis Ababa, Ethiopia - Ezra Shimeles; Melaku Tilahun; Tsegaye Hailu; Fikre Enquselassie; Abraham Aseffa; Alemayehu Mekonnen; Getachew Wondimagegn (Advances in Public Health)
Background. Tuberculosis (TB) has continued to be a major health problem globally, in spite of the efforts to improve the diagnosis, treatment, and prevention. It affects millions of people each year and stands as the second cause of death due to infectious disease in the world. Early case finding and timely initiation of treatment is essential to ensure effective control of the disease as late diagnosis and treatment can aggravate the disease and result in poor outcomes and increase chances of transmission. Although TB services are supposed to be provided free of charge, TB affected families incur different types of costs in the process of seeking care, which might include health and nonhealth related costs. TB programs need to identify the underlying factors for delay and related expenditure for TB related services, in order to devise an effective strategy to reduce them. Therefore, the study aimed to assess the time interval between developing TB symptom until patients start anti-TB treatment and associated cost incurred by patients and families. Methods. This cross-sectional study was conducted among pulmonary TB patients who are bacteriologically confirmed, whose age is above 15 years and diagnosed at health centres in Addis Ababa. Results. The median time interval between onset of symptom and commencement of treatment was 4 weeks (IQR: 3, 6). Most patients with TB symptoms visited several health facilities before the final diagnosis was confirmed, the median number of visits being two, and only 48.8% were diagnosed on their first visit. Hence, they spent a lot of their limited resource in search of getting the right diagnosis. The total combined expenditure for all the visits was estimated to be median (IQR) 172.65 birrs (12, 671). Two variables were found to show statistically significant association with higher expenditure. Respondents who have good level of knowledge about TB are less likely to spend more than the median expenditure almost by a fifth compared to those with limited knowledge on TB, (adjusted odds ratio (AOR) = 0.2, with 95% confidence interval (CI): 0.06, 0.84). Patients who visited public hospitals were almost three times and those who visited private health facilities almost four times more likely to pay more than the median total expenditure, compared to those who visited health centre, AOR (95% CI) = 2.8 (1.53, 5.19) and AOR (CI) of 3.86 (1.06, 14.03), respectively. Conclusion. Patients with TB symptoms visit several health facilities till they are diagnosed, the median duration from onset of symptom till commencement of TB treatment being 4 weeks. It was noted that they face major expenses in the process of navigation to the right care. Two variables had statistically significant association with high pre-diagnosis expenditure, where patients with good level of knowledge about TB are less likely to spend more than the median, while patients who visited public hospitals or private health facilities had very high expenses. Improved public awareness about TB, minimizing service charges and other related fees, and further improvement in increasing access to services could reduce the length of time and expense for TB patients and their families. It is recommended to build capacity of health service providers to update them on programmatic approaches and latest diagnostic algorithm. It is important to strengthen public private partnership for TB services.